AN AQUACULTURE DISRUPTED BY DIGITAL TECHNOLOGY - Setiyowati, Harlis; Thalib, Supriadi; Setiawati, Ratna; Nurjannah, Nurjannah; Akbariani, Nurhaliza Vania (AUSTENIT, 2022)
Fish farming as a primary protein source is significantly more efficient than other protein sources, and demand for fish continues to climb. The future of fish farming is brighter, more traceable, and more profitable. This research aims to learn everything there is to know about the Internet of Things (IoT) systems, including their technology, protocols, and potential hazards. According to the literature, 3D printing, robotics, drones, sensors, artificial intelligence, augmented reality (AR), virtual reality (VR), and blockchain are the digital technologies affecting aquaculture. A wide range of industries is adapting and using it.